Global slowdown and the Indian Economy - Chitre, Vikas (2003)
While there may have been some effect of the current global slowdown on economic activity in India, poor performance of agriculture has perhaps been more responsible for the Indian economic slowdown in recent years. Thus domestic factors such as agricultural growth can be neglected only at our own peril. With the information technology industry set to be a major vehicle for productivity growth, India must be prepared to withstand the increased possibility of output volatility through upswings and recessions. And as it increasingly meshes with the globalised trading and financial system, India's own financial system must be strengthened to withstand asset price shocks with policies geared to take quick remedial measures. - Reproduced.
Keywords: Economic growth - India; Economic growth